A copper(ii)-based MOF film for highly efficient visible-light-driven hydrogen production. Issue 19 (22nd April 2016) - Zhao, Jingshu; Wang, Yin; Zhou, Junwen; Qi, Pengfei; Li, Siwu; Zhang, Kexin; Feng, Xiao; Wang, Bo; Hu, Changwen
Abstract : A copper(ii )-based MOF film (MOF-199/Ni) prepared by electrodeposition shows exceptionally high photocatalytic hydrogen production rates with and without Pt as the co-catalyst. Abstract : A copper(ii )-based MOF film (MOF-199/Ni) prepared by electrodeposition shows exceptionally high photocatalytic hydrogen production rates of 8000 μmol h −1 g −1 (based on the mass of MOF-199) and 24 400 μmol h −1 g −1 with Pt as the co-catalyst and eosin Y as the photosensitizer. The activity is one of the highest among all the reported MOF-based hydrogen production systems. With nickel foam as a substrate, the deactivation of MOF-199 is largely alleviated, and the MOF-199/Ni film can be easily recycled and reused after photocatalytic hydrogen production.